EVALUASI PELAKSANAAN PROGRAM PEMBINAAN KEMANDIRIAN WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KELAS IIB SLEMAN - Retno, Jayanti; Sri, Utami (CITIZEN CHARTER, 2024)
This research aims to determine the implementation of the independence development program for Correctional Inmates (WBP). WBP training that does not deter the perpetrators results in many of them repeating the crimes they have committed after they are released from Correctional Institutions (Lapas). Class IIB Sleman Prison is a UPT which aims to form WBP so that they are accepted back into society. For this reason, the independence development program aims to provide skills to inmates and improve their social functioning after leaving prison. In general, the aim of this research is to discuss the evaluation of the implementation of the independence development program. This research uses qualitative methods by collecting data using observation, documentation and interviews with fourteen informants. The theory used in this research is the process evaluation theory proposed by Adi (2001: 128). Process evaluation is carried out based on four components, namely best practice standards, policies, process objectives, and client satisfaction. The research results show that operational standards and service delivery processes are in accordance with statutory provisions. Service targets and human resources have worked in accordance with applicable policies. The long-term goals of the program have not been fully achieved. The officers have served quickly and have good care. The facilities available are still not in line with the number of WBPs, and the types of coaching programs offered are still not in line with the WBPs' interests. The Class IIB Sleman prison development program needs to be maintained in order to achieve short-term and long-term goals. Sleman Class IIB Prison needs to improve the skills of WBPs and expand the marketing of WBP products. Apart from that, correctional officers need to develop independence, so that officers can focus more on efforts to improve services to inmates. Considering the importance of the objectives of the self-reliance development program being implemented, it is hoped that inmates can take advantage of the development program while in prison.   Keywords: Process Evaluation, Development, Correctional Inmates, Correctional  Institutions